Validity of EQ‐5D‐5L, Skindex‐16, DLQI and DLQI‐R in patients with hidradenitis suppurativa. (2nd July 2020) - Gergely, L.H.; Gáspár, K.; Brodszky, V.; Kinyó, Á.; Szegedi, A.; Remenyik, É.; Kiss, N.F.; Bató, A.; Péntek, M.; Gulácsi, L.; Sárdy, M.; Bánvölgyi, A.; et al.
Abstract: Background: Numerous generic, skin‐ and disease‐specific health‐related quality of life (HRQoL) measures are available for patients with hidradenitis suppurativa (HS). Yet, robust psychometric evidence is lacking in many aspects of these outcome measures. Objectives: We sought to determine convergent and known‐groups validity of multiple generic and skin‐specific HRQoL measures and to identify predictors of impaired HRQoL in patients with HS. Methods: Between 2017 and 2019, a multicentre cross‐sectional study was carried out involving 200 consecutive HS patients. HRQoL outcomes included the EQ‐5D‐5L, EQ visual analogue scale (EQ VAS), Skindex‐16, Dermatology Life Quality Index (DLQI) and DLQI‐Relevant (DLQI‐R). Disease severity was graded by HS‐Physician's Global Assessment (HS‐PGA) scale and the Modified Sartorius scale (MSS). Results: Overall, 77%, 56%, 51%, 46% and 28% reported problems in the pain/discomfort, usual activities, anxiety/depression, mobility and self‐care dimensions of EQ‐5D‐5L. Mean ± SD EQ VAS, DLQI and DLQI‐R scores were 64.29 ± 22.68, 11.75 ± 8.11 and 12.19 ± 8.33, respectively. Skindex‐16 responses indicated that the emotional burden of HS (64.55 ± 29.28) far exceeded those of functioning (49.40 ± 34.70) and physical symptoms (46.74 ± 29.36). EQ‐5D‐5L, EQ VAS, DLQI, DLQI‐R and Skindex‐16 total scores had moderate or strong correlations with each other (range: |0.487| to |0.993|), weak or moderate correlations with HS‐PGA (|0.350| to |0.433|) and weak correlations with MSS (|0.324| to |0.389|). DLQI‐R slightly outperformed DLQI both in terms of convergent and known‐groups validity. Being female, lower education level, more severe disease and genital involvement were associated with worse HRQoL (P < 0.05). Conclusion: This study provides high‐quality evidence that among skin‐specific outcomes, the DLQI, DLQI‐R and Skindex‐16, and among generic instruments, the EQ‐5D‐5L are suitable to be used in HS patients. In future research, we recommend the use of existing well‐validated HRQoL tools instead of developing new measures for each study. The development of composite measures that combine physician‐ and patient‐reported outcomes is not supported by evidence in HS. [Correction added on 25 July 2020, after first online publication: in the Abstract section, the ± signs were missing and have been added to this version.]